(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to reveal: 1. The Influence of Organizational Culture on Teacher Work Commitments; 2. The influence of Work Motivation on Teacher Work Commitment and; 3. The influence of Organizational Culture and Work Motivation together on MAN Commitment Work Teacher 2 Model Medan. This study uses a quantitative approach to the correlational model. The population of this research is all of MAN 2 Model Medan teachers, amounting to 160 people. Samples were taken by using random sampling and obtained a sample of 60 people. The research data were collected using a Likert scale model questionnaire that had been analyzed for validity and reliability. Data collected through questionnaires were then analyzed using correlation and multiple regression techniques with the help of SPSS version 20. The results of the study showed that: 1. Organizational Culture significantly influences the Work Commitment of MAN 2 Model Medan by 61.5%. This means that the better teacher professionalism, the better the performance; 2. Work Motivation has a significant effect on MAN 2 Model Medan Teachers’ Work Commitments by 14.8%. This means that if the teacher’s work motivation is sincerely followed, it will increase the Teacher’s work commitment; 3 Organizational Culture and Work Motivation together significantly influence the Work Commitment of MAN 2 Model Medan teachers by 63.4%. This means that both of these factors determine whether or not the Teacher’s Work Commitment is good; if both of these factors are good, the Teacher’s Work Commitment will get better too